A review of the safety and efficacy of bariatric surgery in adults over the age of 60: 2002–2013. Issue 7 (4th March 2015) - Caceres, Billy A.; Moskowitz, Dana; O'Connell, Theresa
Abstract Purpose The purpose of this review is to compare outcomes of bariatric surgery in adults over 60 to younger patients. This analysis is important to determine if nurse practitioners (NPs) and other providers should recommend bariatric surgery to obese older adults. Data sources This review included 15 studies published between 2002 and 2013. Conclusions Although older adults seem to experience less weight loss, bariatric surgery has potential benefits for these patients. Significant improvements in hypertension, diabetes, and, to a lesser extent, dyslipidemia are noted. Mortality and surgical complications in older adults are low, while differences in length of hospital stay are inconclusive. Implications for practice The risks of bariatric surgery in older adults need to be carefully evaluated based on individual medical condition. Overall the evidence suggests that bariatric surgery can be safely performed in older adults but more research is needed to determine which older adult patients are the best candidates for bariatric surgery. As bariatric surgery among older adults increases, interdisciplinary teams will continue to serve an important role in the management of bariatric surgery patients. NPs must be aware of trends in this emerging population of bariatric surgery patients.